Effect of different feeding-feed deprivation time on feed intake, growth and waste output of largemouth bass (Micropterus salmoides) - HUANG Di; REN Xing; WU Yubo; CHEN Jianming; WANG Yan (浙江大学学报. 农业与生命科学版, 2017)
Compensatory growth is described as a phase of accelerated growth when the fish were under favorable circumstances after a period of growth depression, which was widely investigated in the past decades all around the world. Largemouth bass (Micropterus salmoides) is a carnivorous fish species of commercial importance to freshwater aquaculture industry, which is now widely cultured in Guangdong, Zhejiang and Jiangsu provinces.Researches about nutrition requirements have been established a lot in the past decades, however, quite rarely on compensatory growth and feeding regime of largemouth bass. In order to improve the feeding regime of largemouth bass, the research was conducted.An 8-week feeding trial was conducted in an indoor re- circulating system to examine the effect of different regimes of feeding and feed deprivation on feed intake, growth, feed utilization, body composition and waste output of juvenile largemouth bass. Three treatments were designed, in which one group was fed with a formulated feed twice daily (S0), one group was fed for 3 days and then deprived of feed for 1 day (S1), and one group was fed for 7 days and then deprived of feed for 1 day (S2).The results showed that the feed intake, body mass gain and feed conversion ratio (FCR) decreased with the increase of the days of feed deprivation. However, no significant difference was found in nitrogen retention efficiency, phosphorus retention efficiency, condition factor, hepatosomatic index, contents of protein and lipid in whole body, and waste output of nitrogen and phosphorus among the treatments. At the end of the feeding trial, final body mass and mass gain were higher in S0 than in S1, while they were higher in S2 than in S1. During feeding, both feed intake and specific growth rate were lower in S1 and S2 than in S0, while no significant difference was found in nitrogen retention efficency and feed convension ratio between S0 and S1 or S2.The above results indicated that largemouth bass exhibited partial growth compensation when fed with the feeding regimes as S1 and S2, and the mechanism of the compensatory growth is attributed to the increased feed intake during re-feeding. According to the results, when using the feeding regime in pond culture of largemouth bass, the optimal ratio between the days for feeding and feed deprivation should be 13d/1d.